Kaamulan, magtipok tang tanan!: A Cross-cultural Study on the Indigeneity of Festival in Bukidnon - Pandapatan, Alican M.; Pandapatan, Sittie Aina T.; Hussain, Basmah S. (LITPAM, 2026)
This study investigates the indigeneity of the seven tribes of Bukidnon province through the Kaamulan Festival 2025. The festive celebration brings not only entertainment but also an exploration to know about the indigenous people and their culture. To carrried out the study, the researcher employed the ethnographic research method to describe the observed activities. A casual interview was done to few locals encountered. The immersion involved the use of field notes, cameras, and audio/video records. The findings discovered the participation from the seven tribes gathering in Malaybalay City is equally given importance in the celebration. Their presence through showcasing their practices, rituals, dances, and songs through performances helped to understand the Kaamulan festival. The festival is comprised of various events and exhibitions signifying unity. Primarily, the highlights of the Kaamulan is centered to ‘piniliyapan’, ‘pamalabag’, ‘pangampo’, etc. in branding its event. Authentic experience is engrained in the performances due to the real members of the indigenous people. They are performing their usual daily activities back home in their village. However, the authenticity of few and well-choreographed movements might eradicate the original and naturalness of particular cultural performance. This implies a delimma on authenticity. Hence to explore this, it is recommended to fully validate movements and actions to the people themselves. Their authority entails respect and establishing orientation to the multiple stakeholders who organize the Kaamulan.